Clinicopathological characteristics and outcomes of PLA2R related idiopathic membranous nephropathy in patients with seronegative PLA2R antibodies - Xue Li; Yang Shen; Yanchun Li; Lijie Ma; Qianmei Sun (Renal Failure)
Background Idiopathic membranous nephropathy (IMN) with deposits of phospholipase A2 receptor (PLA2R) antigen in glomerular tissue (GAg+) but no circulating serum PLA2R antibody (SAb−) has been reported. However, little is known about the clinicopathological characteristics and prognosis of this subtype.Methods A total of 74 IMN patients with GAg + identified by kidney biopsy were enrolled in this study. We categorized patients into two groups based on the presence or absence of serum PLA2R antibody. Data on clinical features, pathological features, and outcomes were collected. Kaplan–Meier analysis of complete remission (CR) and partial remission (PR) comparing SAb−/GAg + and SAb+/GAg + patients. Cox proportional hazards models was used to examine factors associated with CR and PR.Results Among 74 IMN patients, 14 were SAb−/GAg+. Compared with SAb+/GAg + patients, SAb−/GAg + patients presented with higher levels of albumin, lower levels of cholesterol and low density lipoprotein cholesterol (all p < .01), but similar pathological manifestations of kidney biopsy. Multivariate logistic analyses indicated that low albumin (0.79 [95%CI: 0.66–0.95], p = .01) and high cholesterol (1.81 [95%CI: 1.02–3.19], p = .04) were correlated with seropositivity of PLA2R antibody. SAb−/GAg + patients exhibited a significantly higher probability of CR (p = .03) than patients who were SAb+/GAg+. However, no difference was found in the PR rate. Cox regression analyses showed that compared to SAb+/GAg + patients, SAb−/GAg + was more predictive of complete remission (4.28 [95%CI: 1.01–18.17], p = .04).Conclusion IMN with PLA2R staining on kidney biopsy but without serum PLA2R antibody has milder clinical manifestations and a better prognosis.